DEVELOPING METACOGNITIVE AND LINGUACULTURAL COMPETENCE OF PRE-SERVICE LANGUAGE TEACHERS IN AN AIENHANCED LEARNING ENVIRONMENT - Beisembayeva A.D.; Utemgaliyeva А. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This study explores the development of metacognitive and linguacultural competence among pre-service language teachers in an AI-enhanced learning environment. It examines how integrating artificial intelligence tools fosters learners’ ability to plan, monitor, and evaluate their learning processes while deepening their understanding of cultural and linguistic contexts. The research emphasizes the importance of reflective practices, adaptive learning strategies, and culturally responsive pedagogy supported by intelligent technologies. By combining metacognitive skillbuilding with linguacultural awareness, the study aims to prepare future language teachers for dynamic, technology-driven classrooms. The findings are expected to offer innovative approaches to teacher education, contributing to more effective and culturally sensitive language teaching practices in the digital age.
Keywords: metacognitive competence; linguacultural competence; pre-service language teachers; artificial intelligence; reflective learning